Factors influencing job satisfaction of civil engineers in local government of Nepal - Koirala, Madhav Prasad; Dhungana, Bharat Ram; Gajurel, Ujjwal; Dhungana, Subigya; Giri, Om Prakash (Advances in Engineering and Technology: An International Journal, 2026)
Job satisfaction of civil engineers plays a crucial role in enhancing the performance of infrastructure development projects. This study examined the factors associated with job satisfaction of civil engineers with reference to local government of Nepal. A cross-sectional survey of purposefully selected 169 civil engineers involved in Gandaki Province of Nepal were included in the study. Five points Likert scale structured questionnaires were used to measure the factors influencing job satisfaction of civil engineers based on the single global rating method (SGRM) and summation of job factor method (SJFM). Regression analysis shows pay structure, career development, supervision, fringe benefits, reward provision, operating procedures, teamwork, working environment, and communication system have a positive and significant impact on job satisfaction among the civil engineers in the local government. This study finds a low level of job satisfaction for civil engineers working in the local level government. Productivity of civil engineers and performance of infrastructure projects in local governments can be improved through job satisfaction techniques. Local government may adopt job satisfaction policy for local level engineers to enhance the construction work performance in local government.